Conceptualization of Economic Right For Small Traders at Traditional Market In Indonesia - Mustapa Khamal Rokan (Universitas Islam Negeri Jakarta, 2017)
Transnational corporations trading power has been challenged human right condition in Indonesia. There are many small trader (read:traditional market) have been marginalized. This paper conceptualize right ofsmall traders to justice market by means seeing traditional market cases. This paper is using qualitative method research by statute approach and also use primair data at the field by means interview trader at tradition market. This study shows that Indonesian law market doesn’t opimize yet to protect and maintain traditional market Indonesia. The regulations give the local leaderto make the policy about it. Indonesian law instrument especial human rightlaw and law of market must be up dated to maintain the vulnarable group liketraders at traditional market. DOI: 10.15408/ajis.v17i1.6231